Source Rock Assessment of Naokelekan Formation in Iraqi Kurdistan - Abdula, Rzger A. (Sulaimani Journal for Pure and Applied Sciences, 2017)
The Callovian-Kimeridgian Naokelekan Formation is a heterogeneous sequence consisting principally of bituminous shales with bituminous limestone and dolomitic limestones. It is 48 m thick maximally in some parts of the area. One hundred forty four rock and cutting samples from six outcrops and eight boreholes in different parts of Iraqi Kurdistan have been studied using the Rock-Eval technique with the primary purpose of assessing their potentiality as promising source rocks for petroleum. The outcomes of the Rock-Eval study for examined samples shows that TOC ranges from 0.4 to 18.8 wt. % and types II and III kerogens are the main components of organic matter. Qualitative evaluations are also done by textural microscopy used in assessing amorphous organic matter for palynofacies. The organic matters are mature that have thermal alteration index of 2.6-3.2 by Pearson's scale with palynomorphs of dark orange and light brown colors and Tmax ranges between 434 to 493ºC. Thus the Naokelekan Formation can be considered as a source rock for generation and expulsion of oil and/or gas that has been charged largely oil fields in the area. Maturity increases toward the northeastern part of the studied area. Furthermore, the study revealed that Naokelekan Formation is within dry gas and/or late oil zone in the eastern part, early oil window in the central part and immature in the western part of the studied area.
Keywords: Naokelekan Jurassic,Source rock; Kerogen; Maturity; Kurdistan